2019
DOI: 10.4236/ajmb.2019.92003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Tissue Distribution of Troponin I from the Japanese Pearl Oyster, <i>Pinctada fucata</i>

Abstract: Troponin is a complex of three proteins (troponin I, troponin C, and troponin T) that binds Ca 2+ and is a thin filament-associated regulator of vertebrate striated muscle contraction. The function of troponin I (TnI) in vertebrates has been extensively characterized, but its role in molluscan muscles has not yet been elucidated. Our previous work suggested that the troponin C subunit has a role in adductor phasic muscle but not in catch muscle. Here, we investigated the molecular characteristics of TnI from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Pifuc-TnC and Pifuc-TnI are predominantly expressed in phasic muscle, suggesting that Pifuc-Tn proteins in phasic muscle operate within a regulatory system [14] [15]. Therefore, we speculated that Pifuc-TnT interacts with Pifuc-TM1 and not Pifuc-TM2.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Pifuc-TnC and Pifuc-TnI are predominantly expressed in phasic muscle, suggesting that Pifuc-Tn proteins in phasic muscle operate within a regulatory system [14] [15]. Therefore, we speculated that Pifuc-TnT interacts with Pifuc-TM1 and not Pifuc-TM2.…”
Section: Introductionmentioning
confidence: 94%
“…To examine the molecular mechanism of thin filament-linked regulation of molluscan muscle contraction, our studies have centered on the adductor muscle Tn subunits. To this end, P. fucata TnC (Pifuc-TnC) and TnI (Pifuc-TnI) have recently been described [13] [14] [15]. Pifuc-TnC has four EF-hand motifs, sites I-IV, and, like other molluscan TnCs [16] [17] [18], only site IV is able to bind Ca 2+ [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we have used P. fucata as a model system to elucidate the molluscan muscle regulatory system. We recently performed molecular characterization of TnC and TnI from P. fucata, and suggested that Tn may participate in the regulation of the phasic adductor muscle not in catch muscle, because they are predominantly expressed in the phasic muscle [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%